ON THE CONCEPT AND RELATED TERMS (Scientific journal of the Fergana State University, 2026)
This article analyzes the linguistic essence of the concept notion and the system of related terms (conceptosphere, nominative field, nominative density, etc.). Within the framework of the conducted research, various scientific interpretations of the concept, its role in cognitive and linguocultural approaches, and its usage in Uzbek linguistics are elucidated. The results of the analysis prove that the concept, as a multifaceted mental category, serves as an important theoretical tool in studying the interrelation between language and thought, as well as between language and culture.